Sentinel lymph node identification in early stage ovarian cancer: is it still possible after prior tumor resection? - Pim Laven; Roy Kruitwagen; Petra Zusterzeel; Brigitte Slangen; Toon van Gorp; Jochem van der Pol; Sandrina Lambrechts (BMC, 2021)
Abstract Objective Sentinel lymph node (SLN) detection in ovarian cancer is feasible when tracers are injected before the pathological ovary is resected. This study aims to investigate whether the SLN identification is also feasible in patients whose ovarian tumor has already been resected with injection of the tracer into the ovarian ligaments stumps, i.e. in the event that a frozen section confirms malignancy. Methods Patients who underwent laparotomy with frozen section confirming an ovarian malignancy, and those who underwent a second staging laparotomy after prior resection of a malignant ovarian mass, were included. Blue dye and a radioactive isotope were injected in the stumps of the ligamentum ovarium proprium and the ligamentum infundibulo-pelvicum. After an interval of at least 15-min, the sentinel node(s) were identified using either the gamma-probe and / or blue dye. Results A total of 11 patients were included in the study, the sentinel node (SLN) procedure was completed in all 11 patients. At least one SLN was identified in 3 patients, resulting in a rather low detection rate of 27,3%. Conclusion In this study we showed that SLN procedure after (previous) resection of the tumor seems inferior to detect sentinel nodes when compared to injection of the tracer in the ovarian ligaments before tumor resection. Trial registration NCT02540551